How Does Nuclear Energy Affect Environmental Pollution? Evidence from the United States - Melike Atay Polat; Buket Savranlar; Ferhan Arslan (Faculty of Economic and Business, 2024)
Research Originality: Nuclear power plant installation activities, which have gained momentum since the 1970s, have made the use of nuclear energy widespread, and especially the US ranks first in the world in the nuclear energy use. This article contributes to the existing literature on environmental economics by incorporating environmental technologies and globalization into the investigation of the impact of nuclear energy on environmental pollution. Research Objectives: The aim of this study is to analyze the effects of nuclear energy consumption, environmental technologies and globalization on environmental pollution in the US.Research Methods: The paper use ARDL approach with the data of 1970-2018 period. Empirical Results: According to the findings, nuclear energy consumption negatively affects environmental quality in the US both in the short and long run. On the contrary, while environment-related technologies contribute positively to environmental quality with a reducing effect on carbon footprint in the long run. Also, globalization has an insignificant effect on environment in both short and long run.Implications: It is thought that environmental quality will improve as a result of supporting environmental technologies and exchanging nuclear energy with renewable energy sources in the US.JEL Classification: Q43, C32How to Cite:Atay Polat, M., Savranlar, B., Arslan, F. (2024). How Does Nuclear Energy Affect Environmental Pollution? Evidence from US. Etikonomi, 23(2), 511 – 526. https://doi.org/10.15408/etk.v23i2.37692.